PENGARUH NET INTEREST MARGIN, NON-PERFORMING LOAN DAN CAPITAL ADEQUACY RATIO TERHADAP RETURN ON ASSET BANK ASING TAHUN 2018 - 2022 - Yuniarti, Rita; Sari, Diana; Rusmawan, Wedi; Nuryaman, Nuryaman; Fadjar, Achmad; Silviana, Silviana (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
Decreasing and fluctuating ROA shows that the bank's performance is still not good, according to the OJK Research Director (2022), the banking sector's ROA start to increase but still not optimal. This study aims to empirically examine the effect of net interest margin, non-performing loans, and capital adequacy ratios on return on assets. The population in this study are foreign banks 2018-2022 with a sample of 10 banks in the good category according to the OJK. The results showed that Net Interest Margin (NIM) had a significant and positive effect on Return on Assets (ROA), Non-performing loans (NPL) had a significant and negative effect on Return on Assets (ROA), while Capital Adequacy Ratio (CAR) had no significant effect on Return on Assets (ROA). Keyword: Net Interest Margin, Non-Performing Loan, Capital Adequacy Ratio, Return on Assets